PENGEMBANGAN LITERASI DIGITAL GURU PAUD PADA ERA REVOLUSI INDUSTRI 4.0 BERBASIS TECHNO-PEDAGOGY APPROACH DI KOTA BANDUNG - ocih setiasih; Rita Mariyana; Wawan Setiawardani (Jurnal Pasca Dharma Pengabdian Masyarakat, 2022)
Today the development of information and communication technology is increasingly rapid in the era of the industrial revolution 4.0 in Indonesia. This era is also known as the disruptive era, where information is abundant and easily accessible to almost all groups. However, the development of information and communication technology has not been matched by the digital literacy of the people. Referring to the Global World Digital Competitiveness Index data, Indonesia is ranked 56th out of 63 countries. Even though Indonesia is a large number of internet users, namely 171 million people, its digital literacy is far behind. This fact also correlates with the role of PAUD teachers as educators who facilitate the growth and development of their students. PAUD teachers need to have good digital literacy as an effort to build broad insights so that it becomes a multiliterate learning resource for their students. Based on these problems, it is necessary to develop digital literacy for early childhood teachers, especially in Bandung. This community service aims to provide learning and guidance based on the Techno-pedagogy Approach. The target audience for this community service is PAUD teachers in Bandung. Through this digital-based service, it is expected to be able to provide a vehicle for flexible access to knowledge so that participants can focus more on learning the content provided. Besides, our long-term hope from this activity is to improve the digital literacy skills of early childhood educators which then have an impact in terms of teaching in class.